2001
DOI: 10.1143/jjap.40.1528
|View full text |Cite
|
Sign up to set email alerts
|

Mass Effect of Etching Gases in Vertical and Smooth Dry Etching of InP

Abstract: We compared several kinds of etching gases in inductively coupled plasma (ICP) and electron cyclotron resonance (ECR) plasma etching processes for investigating the etching performance. It was found that a heavy etching gas such as SiCl4 plays an important role for smooth etching of InP, which is independent of ICP and ECR plasma sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…This is consistent with similar observations reported with pure Cl 2 chemistry. 16 We furthermore evidenced that the carrier material also has a strong influence on the etching anisotropy. obtained even with the aluminum carrier at this high ICP power.…”
Section: B Influence Of Carrier Materialsmentioning
confidence: 68%
“…This is consistent with similar observations reported with pure Cl 2 chemistry. 16 We furthermore evidenced that the carrier material also has a strong influence on the etching anisotropy. obtained even with the aluminum carrier at this high ICP power.…”
Section: B Influence Of Carrier Materialsmentioning
confidence: 68%
“…30,31 Similarly, from an InP carrier one may expect PCl 3 gas to participate in the etching process. Therefore, to elucidate the impact of the carrier on etching, experiments were performed with both Si and InP carriers.…”
Section: Inp Vs Si Carriermentioning
confidence: 99%
“…10 The most obvious choice of passivation agent is aluminum oxide which is formed by background oxygen and residual moisture in the chamber. According to Urushido et al 16 and Matsutani et al, 21,22 molecular SiCl x radicals and molecular SiCl x + ions are formed during etching of Si with Cl 2 plasma. 10,11 Therefore aluminum oxide is very etch-resistant in Cl 2 plasma compared to gallium oxide, These results were related to the ability of BCl 3 to scavenge the oxygen in the chamber preventing the formation of the aluminum oxide and also increased physical sputtering by heavy BCl x + ions.…”
Section: A Influence Of Coverplate Materialsmentioning
confidence: 99%
“…10,11 Therefore aluminum oxide is very etch-resistant in Cl 2 plasma compared to gallium oxide, These results were related to the ability of BCl 3 to scavenge the oxygen in the chamber preventing the formation of the aluminum oxide and also increased physical sputtering by heavy BCl x + ions. 21,22 It was observed that the etch rate of the SiO 2 mask was higher when using the quartz coverplate together with the Si wafer. 13 It was also mentioned that aluminum oxide could be removed in BCl 3 discharge.…”
Section: A Influence Of Coverplate Materialsmentioning
confidence: 99%